Temporal and spatial patterns in the chemistry of wet deposition in Southern Alps. (December 2016) - Rogora, M.; Colombo, L.; Marchetto, A.; Mosello, R.; Steingruber, S.
Abstract: In the last decades, in Europe a large effort was carried out to reduce sulphur and nitrogen emission in the atmosphere, in order to improve air quality and reduce the acidity of atmospheric deposition and the amount of nitrogen compounds it carries to terrestrial and aquatic ecosystems. This resulted in a sharp decrease in the deposition of sulphate and acidity, while until recently a decrease of the atmospheric load of nitrogen compounds was not evident. In this paper, we focus on the subalpine and alpine areas in North-Western Italy and Southern Switzerland (Canton Ticino), receiving high deposition of atmospheric pollutants transported from emission sources in the Po Valley, one of the most urbanised and industrialised areas of Europe. Long-term studies, covering a 30-year period (1984–2014), were carried out on the chemistry of atmospheric deposition in this area and its effects on surface water bodies through a cooperation between Swiss and Italian research institutions. A total of 14 atmospheric deposition wet-only sampling sites operate in this area, covering a wide latitudinal and altitudinal range (about 200–1900 m a.s.l.). A spatial gradient in the deposition of sulphate and nitrogen compounds was evident both in the 1990s and in recent times (2008–2012), with highest values in the south-eastern part of the area, close to the major emission sources. Deposition also varied depending on local topography. The analysis of long-term trends revealed a large proportion of significant decreasing trends in the concentration of both sulphate and nitrogen compounds. Deposition changes were less evident, due to the high interannual variability in the data, caused by the highly variable precipitation amount, ranging from 1200–1300 mm in dry years to 3000 mm in wet years. Sulphate concentrations and deposition decreased steadily since the 1980s, while ammonium and nitrate showed a widespread decrease only in the most recent period (after 2006). However, nitrogen wet deposition is still high with respect to critical loads: inorganic N deposition ranges from 60–70 meq m −2  y −1 (as the sum of ammonium and nitrate) at the alpine sites to 120–140 meq m −2  y −1 at the southern lowland sites. Deposition of ammonium has acquired an increasing importance in time, especially at the southern, more polluted sites: the relative contribution of reduced N to wet N deposition passed from about 50% in the early 1990s to 56–57% in recent years. The observed temporal changes in nitrogen deposition followed the emission decrease but with a delay. This aspect may be relevant in monitoring the effects of emission reductions as a result of the enforcements of international and national regulations. Highlights: A trend analysis of atmospheric deposition in an area south of the Alps is presented. Ammonium and nitrate deposition decreases only in the most recent period (after 2005). Nitrogen wet deposition is still high, ranging from 60–70 meq L −1 to 120–140 meq L −1 . Precipitation amount is relevant in the temporal and spatial patterns of deposition. Alkaline rain events markedly contribute to the deposition of base cations and alkalinity.